2021
DOI: 10.1002/fsn3.2121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of probiotic adjunct cultures on the characteristics of low‐fat Feta cheese

Abstract: There are different methods that have been recently applied to develop a process to manufacture low‐fat Feta cheese (LFC) with acceptable flavor and texture. The objective of this study was to produce LFC from skim buffalo's milk (SBM) using Streptococcus thermophilus (ST) and Lactobacillus bulgaricus (LB) as control LFC (T1) incorporated with other probiotic adjunct cultures (PAC), such as Lactobacillus casei (LBC) in T2, Bifidobacterium bifidum (BB) in T3, and Lactococcus lactis subsp. lactis (LL) in T4. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
2
15
2
Order By: Relevance
“…This ratio was 1.4 and 2.5 in Feta-type cheese made from MCC with 6% and 9% protein, respectively. The TS and TP of Feta-type cheese made from MCC were similar to that in typical Feta-type cheese (30-50% and 13-20%, respectively), as reported in previous studies [4][5][6][42][43][44][45]. No differences were found in the salt and ash contents of Feta-type cheese (approximately 11% and 12%, respectively).…”
Section: Compositionsupporting
confidence: 87%
“…This ratio was 1.4 and 2.5 in Feta-type cheese made from MCC with 6% and 9% protein, respectively. The TS and TP of Feta-type cheese made from MCC were similar to that in typical Feta-type cheese (30-50% and 13-20%, respectively), as reported in previous studies [4][5][6][42][43][44][45]. No differences were found in the salt and ash contents of Feta-type cheese (approximately 11% and 12%, respectively).…”
Section: Compositionsupporting
confidence: 87%
“…thermophilus containing cheese. Ahmed et al (2021) reported lower numbers of about 6.6 cfu/g in low-fat feta cheese in 6%-8% brine solution during 14 days of storage compared with our study. Rhoades et al (2017) found about 8 cfu/g of total lactic acid bacteria and 5-6 cfu/g yeast and molds in Greek Type Feta brined cheese and in our study, lactic acid bacteria and mold yeast numbers were higher than these results.…”
Section: Microbial Analysis Resultscontrasting
confidence: 81%
“…Ahmed et al (2021) reported lower numbers of about 6.6 cfu/g in low‐fat feta cheese in 6%–8% brine solution during 14 days of storage compared with our study.…”
Section: Resultscontrasting
confidence: 74%
“…No, the colonies have been identified as the last period of time. These results are consistent with those obtained by Ahmed et al (2021) Therefore, probiotics can reach the intestines and supply health benefits. (Bosnea et al 2009).…”
Section: Microbiological Analysissupporting
confidence: 93%